First-in-human evaluation of a no-alpha interleukin–2 mutein: safety and preliminary pharmacodynamic and clinical effect - Caballero Aguirrechu, Iraida; Mestre Fernández, Braulio; Soriano García, Jorge Luis; Lim Alonso, Nora; Soto García, Andrés; Fleites Calvo, Vilma; Mariño de la Puente, Daines; Vega Carvajal, Geidy; Ávila Pérez, Jenny Carolina; Mendoza Hernández, Ivis; García López, Elena; Tarinas Reyes, Alicia; et al. (Frontiers in Immunology, 2025)
IntroductionInterleukin 2 (IL-2) is essential for immune system activation. To reduce toxicity and prevent the activation of regulatory T cells (T-regs), a novel IL-2 variant containing 4-point mutations that prevent its interaction with the alpha chain of the receptor was designed. In preclinical studies, the no-alpha mutein preferentially stimulate CD8-T cells and natural killer (NK) cells compared to Tregs. Mutein also showed greater antitumor capacity than the native molecule in several tumor models.MethodsPatients with advanced solid tumors were included in a single-arm dose-escalation Phase I trial. The objectives of this study were to evaluate the safety and identify the recommended phase 2 dose. The effects on the most important immune subpopulations and preliminary objective response were also assessed. The protocol was listed in the National Registry for Clinical Trials (https://rpcec.sld.cu/ensayos/RPCEC00000234-En). Results and DiscussionIn this phase I trial, 13 patients with advanced cancer were treated with five dose levels of IL-2 mutein, from 300 to 2400 IU/kg. The treatment was safe, and the maximum tolerated dose was not reached. Dose escalation did not continue, as a greater clinical and pharmacodynamic effect was observed at intermediate doses. One patient developed a possibly related serious event consisting on ventricular dysfunction and pneumonitis. No toxic deaths or vascular leak syndromes were detected, and the most frequent toxicities were chills, fever, and tachycardia. After treatment, most patients experienced an expansion of the total lymphocyte counts and the CD8-T cells and NK cells.Clinical trial registrationhttps://rpcec.sld.cu/ensayos/RPCEC00000234-En, identifier RPCEC00000234.